Drug Sellers’ Neutralizations of Guiltless Drug Sales and Avoidance of “Drug Dealer” Identities - Dickinson, Timothy (2019)
Background: Despite a wealth of empirical exploration on neutralization theory, several aspects of the theory remain underexplored. For instance, one task of neutralization research is to investigate whether and how neutralizations vary with offender characteristics. A second underexplored area is whether the neutralizations offenders present when directly asked about feelings of guilt are similar or dissimilar to those they have incorporated into their narrative identities described during interviews. A third underexplored issue is whether offenders that exhibit little guilt for committing mala prohibita crimes use neutralizations in a similar manner as those who do not express guilt for committing mala in se crimes. Methods: The present study examines these questions by drawing from data collected from interviews with 33 active drug sellers from St. Louis, Missouri, USA and 30 active drug sellers from Atlanta, Georgia, USA. Results: We find that these offenders’ neutralizations vary by drug type and by differential access to resources. We also find that, in addition to the neutralizations they give when asked about guilt, these offenders also preemptively neutralize feelings of guilt by constructing identities counter to bad “drug dealers” throughout their storied identities. Conclusion: We conclude by suggesting that neutralizations vary by offender characteristics due to the differing background expectancies of offenders’ social groups. We also suggest that neutralizing the repercussions of immoral actions is not always a static, monothematic technique. It is instead an active, complex, and interactional process that occurs as persons make sense of who they are and what they are doing. Finally, we argue that studies of neutralization theory relying on direct, standardized questions or the presentation of abstract vignettes may fail to capture a sizable part of the neutralization process among offenders